Japan–US–China Relations during the Trump Administration and the Outlook for East Asia. (2nd January 2017) - Kawashima, Shin
Abstract : Recent political events, such as the UK decision to exit the EU and the election of Donald Trump to the US presidency, may indicate a transition from globalism to isolationism in world politics. This article reviews Japan-US-China relations and East Asian regional cooperation during the Obama administration and contrasts them with prospects during the Trump administration in the new political climate.